2018
DOI: 10.1021/acs.jafc.7b05921
|View full text |Cite
|
Sign up to set email alerts
|

Application of Copper-Chitosan Nanoparticles Stimulate Growth and Induce Resistance in Finger Millet (Eleusine coracana Gaertn.) Plants against Blast Disease

Abstract: Copper-chitosan nanoparticle (CuChNp) was synthesized and used to study its effect on finger millet plant as a model plant system. Our objective was to explore the efficacy of CuChNp application to control blast disease of finger millet. CuChNp was applied to finger millet either as a foliar spray or as a combined application (involving seed coat and foliar spray). Both the application methods enhanced growth profile of finger millet plants and increased yield. The increased yield was nearly 89% in combined ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(40 citation statements)
references
References 33 publications
(77 reference statements)
2
38
0
Order By: Relevance
“…Nandini et al [26] reported that, when applying 100 ppm of Se NPs, the growth of the plant was not affected and it did not show any phytotoxic effect, similar to the results observed here. Sathiyabama and Manikandan [27] undertook foliar applications of copper nanoparticles-chitosan, resulting in more leaves, a greater height of the stems, and more fresh weight of the plants. Although it has been reported that both Se NPs and Cu NPs can induce changes in plant growth, this is not always the case, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nandini et al [26] reported that, when applying 100 ppm of Se NPs, the growth of the plant was not affected and it did not show any phytotoxic effect, similar to the results observed here. Sathiyabama and Manikandan [27] undertook foliar applications of copper nanoparticles-chitosan, resulting in more leaves, a greater height of the stems, and more fresh weight of the plants. Although it has been reported that both Se NPs and Cu NPs can induce changes in plant growth, this is not always the case, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects of shells or chitin-source treatments on growth promotion and/or host resistance have also been reported for other pathosystems such as cocoa/snail shells/Phytophthora megakarya [9], tobacco/nanochitin/Fusarium spp. [21], chilli/chitosan/Colletotrichum capsica [22], millet/chitosan derivatives/Pyricola grisea [23], tomato/crab shells/Fusarium oxysporum [24] and cocoa/oyster shells/P. megakarya [20] through the possible triggering of biochemical pathways associated with growth promotion and disease resistance [8] [25] [26].…”
Section: Discussionmentioning
confidence: 99%
“…10 We have recently reported a one-pot synthesis of amoxicillin-coated gold nanoparticles that show synergistic antimicrobial activity upon light irradiation; 11 where the antimicrobial mechanism may involve the generation of localized heat and reactive oxygen species (ROS) upon light irradiation. 12,13 The growing interest in the use of environmentally friendly capping agents, as well as, the use of sustainable resources for antimicrobial applications, 14,15 such as food packaging, 16 has led our group towards the use of non-toxic and inexpensive capping agents. 17 Here we explore the use of lignin, the second most abundant natural polymer on earth aer cellulose, as an alternative reducing and capping agent for the synthesis and stabilization of metal nanoparticles for potential applications as antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%